Medical device-related pressure injury prevention related to fixation of nutritional and derivative probes: a best practice implementation project. (11th September 2022) - Saibertová, Simona; Klugarová, Jitka; Klugar, Miloslav; Pokorná, Andrea
ABSTRACT: Objectives: The main objective was to improve the provision of clinical care in pressure injury prevention related to the use of medical devices focused on nasogastric probes. Introduction: The insertion of nasogastric probes could lead to the formation of medical device-related pressure injuries (MDRPI). The risk increases with the length of the probe insertion and is higher in patients in intensive care. MDRPI prevention is mostly based on appropriate skin and mucosa membrane and tissue monitoring and positioning of the medical devices. Methods: The project has been conducted based on JBI Implementation approach for promoting change in healthcare practice. A baseline audit on MDRPI prevention was undertaken and involved 21 nurses and 12 patients using a questionnaire for nurses and a record sheet for patient's monitoring. The intervention included education, clinical practice training, consultation, and other strategies. A follow-up audit was undertaken, including all original participants. Results data on changes in compliance were measured using descriptive statistics embedded in JBI-PACES in the form of percentage changes from baseline. Results: There were significantly improved outcomes across all best practice criteria. The level of knowledge of nurses increased. Skin barrier creams and mass-supplied fixation are now used to prevent skin injuries on the nose. The new monitoring and documentation is more accurate and in line with evidence-based practice. Conclusion: Overall, the project achieved an improvement in evidence-based practice in the prevention of MDRPI in patients with nasogastric probes based on nurses' increased level of knowledge and usage of appropriate preventative measures.